A multi-purpose silicone rubber base material and preparation method thereof
By using high specific surface area nano calcium carbonate in silicone glue base material to replace gas phase white carbon black, the problems of high cost of gas phase white carbon black and coarse nano calcium carbonate particle size are solved, and the effect of reducing production costs and improving mechanical properties is achieved.
Patent Information
- Application Number
- CN202410900381.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-05
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-07-05
AI Technical Summary
In the prior art, gas phase white carbon black has high cost, low filling amount, low applicability, and the existing nano calcium carbonate particle size is relatively coarse, which cannot replace gas phase white carbon black for the production of silicone glue base material.
Using high specific surface area nano-calcium carbonate, nano-calcium carbonate with high specific surface area and good dispersion is prepared through specific crystal form control and surface modification methods, replacing gas-phase white carbon black as the main component of silicone glue base material.
It has achieved the reduction of silicone glue production costs and improved the mechanical properties of silicone glue. The preparation process is simple, the product performance is stable, and it is easy to promote.
Smart Images

Figure CN118685148B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of silicone adhesive preparation, and specifically relates to a multi-purpose silicone adhesive base material and a preparation method thereof. Background Art
[0002] In the prior art, silicone sealant is a type of sealant, which refers to a sealant produced with linear polysiloxane as the main raw material, also called silicone sealant. As a key bonding and sealing material, it is widely used in the field of glass curtain wall, aluminum curtain wall, and stone curtain wall construction technology.
[0003] In the prior art, silicone adhesive is mainly composed of active polysiloxane, inert polysiloxane, fumed white carbon black and calcium carbonate. The market price of fumed white carbon black is high, and the filling amount is low during the production of silicone adhesive, which greatly limits the applicability of fumed white carbon black.
[0004] In the existing technology, calcium carbonate is the cheapest material on the earth, and nano calcium carbonate is the lowest-priced nano material. However, the existing nano calcium carbonate cannot replace fumed silica for use in special sealants due to its coarse particle size (all higher than 30nm). When the particle size of nano calcium carbonate is reduced to below 20nm, nano calcium carbonate has good thixotropy and reinforcement, and can replace reinforcing materials such as fumed silica. Therefore, there is an urgent need for a method for preparing a silicone adhesive base material by replacing fumed silica with nano calcium carbonate, so as to reduce the production cost of silicone adhesive and improve the mechanical properties of silicone adhesive. Summary of the invention
[0005] In order to solve the technical problems in the prior art that when fumed white carbon black is used as an additive to produce silicone adhesive base materials, the fumed white carbon black has high cost, low filling amount, low applicability, and the existing nano calcium carbonate has a coarse particle size and cannot replace the fumed white carbon black to produce silicone adhesive base materials, the present application proposes a multi-purpose silicone adhesive base material;
[0006] In order to solve the technical problem raised in this application, this application also provides a method for preparing a multi-purpose silicone adhesive base material.
[0007] In order to solve the technical problem proposed by the present application, the present application adopts the following scheme: a multi-purpose silicone adhesive base material, which is composed of the following components by weight: 37-62 parts of base adhesive, 18-38 parts of high specific surface area nano calcium carbonate, 5-45 parts of active heavy calcium carbonate, and the base adhesive is 20000mPa﹒s terminal hydroxyl polydimethylsiloxane;
[0008] The method for preparing nano calcium carbonate with high specific surface area comprises the following steps:
[0009] Step 101. After calcium hydroxide emulsion is obtained by thorough reaction of calcium oxide and water, it is removed from impurities and aged to prepare a slurry A with a concentration of 1.0-1.2 mol / L and a viscosity of 800-1000 cP;
[0010] Step 102. After adding the crystal form control agent to the slurry A prepared in step 101, the slurry B is obtained after pre-reaction at 20-23° C. for 20-50 minutes. The slurry B is transferred to a high shear carbonization kettle, and carbonized once under the conditions of lime kiln gas and stirring frequency of 50 Hz. The conductivity of the slurry B is measured at the same time to determine the end point of the primary carbonization reaction. When the end point of the primary carbonization reaction is reached, CaCO is obtained. 3 -Ca(OH) 2 Linear intermediate slurry;
[0011] Step 103. The CaCO prepared in step 102 3 -Ca(OH) 2 The linear intermediate slurry and dispersant were sequentially put into the stirred mill, and secondary carbonization was carried out under the condition of lime kiln gas and stirring frequency of 50 Hz, and CaCO was measured at the same time. 3 -Ca(OH) 2 The pH value of the linear intermediate slurry is used to determine the end point of the secondary carbonization reaction. When the end point of the secondary carbonization reaction is reached, slurry C is obtained;
[0012] Step 104. The slurry C prepared in step 103 is transferred to a modification kettle, and a modifier is added to the modification kettle for reaction. After the reaction is completed, slurry D is obtained. The slurry D is transferred to a finished product tank, and high specific surface area nano calcium carbonate is obtained after filter pressing, dehydration, drying, and depolymerization.
[0013] Furthermore, the preparation method of activated heavy calcium carbonate includes the following steps: 1000 mesh vertical mill large calcite powder and activator are sequentially put into a high-speed mixer at a mass ratio of 100:1-1.5, and the mixture is dispersed at a high speed for 10 minutes at 100-110°C and 2200rpm to obtain the activated heavy calcium carbonate.
[0014] Furthermore, the activator is a mixture of sodium polyacrylate and refined coconut oil in a mass ratio of 1:10-12.
[0015] Furthermore, in step 102, the crystal form control agent is a mixture of glucose and citric acid in a mass ratio of 1:3, and the amount of the crystal form control agent added is 5-8% of the dry weight of calcium carbonate.
[0016] By selecting a mixture of glucose and citric acid as a crystal form control agent, glucose is a short-chain monosaccharide that can be adsorbed on the surface of calcium carbonate crystals to produce fibrous crystal nuclei. Since glucose is a short-chain monosaccharide, the diameter of the fiber crystal nuclei can be effectively controlled. By adjusting the degree of carbonization, CaCO3 rich in fiber crystal nuclei and free calcium ions can be produced. 3 -Ca(OH) 2 The linear intermediate is subsequently combined with calcium ions in the slurry through citric acid and adsorbed on the fibrous crystal nuclei to further control the morphology of the calcium carbonate crystals, promote the production of calcite type, and increase the specific surface area of the nano calcium carbonate crystals in the shape of cubic clusters.
[0017] Furthermore, in step 102, the lime kiln gas temperature is 30-40°C, and the lime kiln gas flow rate is 1.2-1.5m 3 / min, the volume content of carbon dioxide in lime kiln gas is 38-40%.
[0018] Furthermore, in step 102, when the conductivity of slurry B is measured to be 3-4 ms / cm, the primary carbonization reaction reaches the end point, and the introduction of lime kiln gas into slurry B is stopped.
[0019] Furthermore, in step 103, the dispersant maleic anhydride grafted polyisobutylene and sodium hexametaphosphate are mixed in a mass ratio of 1:4, and the input amount of the dispersant is 6.0-10.0% of the dry weight of the nano-calcium carbonate.
[0020] By selecting a mixture of maleic anhydride grafted polyisobutylene and sodium hexametaphosphate as a dispersant, the CaCO 3 -Ca(OH) 2 The dispersion of linear intermediates effectively improves the CaCO 3 -Ca(OH) 2 The contact area between the linear intermediate and the lime kiln gas can effectively control the crystal morphology of nano calcium carbonate crystals and increase its specific surface area.
[0021] Furthermore, in step 103, CaCO 3 -Ca(OH) 2 When the pH value of the linear intermediate slurry was 7.0, the secondary carbonization reached the end point of the reaction and stopped feeding CaCO 3 -Ca(OH) 2 Lime kiln gas is introduced into the linear intermediate slurry.
[0022] Furthermore, in step 103, the lime kiln gas temperature is 30-40°C, and the lime kiln gas flow rate is 0.6-0.8m 3 / min, the volume content of carbon dioxide in lime kiln gas is 35-40%.
[0023] Furthermore, in step 104, the modifier is a mixture of ethylene glycol palmitate and stearic acid in a mass ratio of 1:2-4.
[0024] By selecting a mixture of ethylene glycol palmitate and stearic acid to modify the high specific surface area nano calcium carbonate, the long chain structure of ethylene glycol palmitate and stearic acid can efficiently adhere to the surface of the high specific surface area nano calcium carbonate, thereby improving the dispersibility and stability of the high specific surface area nano calcium carbonate. After being prepared into a silica gel base material, the stability and thixotropy of the base material can be effectively improved.
[0025] In order to solve the technical problem raised in this application, this application also proposes a method for preparing a multi-purpose silicone adhesive base material, comprising the following steps: putting base adhesive, high specific surface area nano calcium carbonate, and active heavy calcium carbonate into a reactor in sequence, reacting for 2-3 hours under the conditions of 100-150°C and -0.08Mpa, and then filling to obtain the silicone adhesive base material.
[0026] Compared with the prior art, this application has the following beneficial effects:
[0027] The present application provides a multi-purpose silicone rubber base material and a preparation method thereof, wherein the silicone rubber base material is composed of a base rubber, high specific surface area nano calcium carbonate and active heavy calcium carbonate, wherein the high specific surface area nano calcium carbonate is prepared by controlling the crystal shape and particle size range of calcium hydroxide with a specific crystal form control agent, and then modified with a surface modifier to improve its dispersibility and compatibility. In the production process of the silicone rubber base material, the high specific surface area nano calcium carbonate has the advantages of high reinforcement, high compatibility and easy processing, can replace gas phase white carbon black, has low implementation cost and high filling amount, and the silicone rubber base material prepared therefrom has strong mechanical properties, simple production process, stable product performance and is easy to promote and implement. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for describing the embodiments.
[0029] Figure 1 It is CaCO in Example 1 of the present application. 3 -Ca(OH) 2 Transmission electron micrograph of the linear middle.
[0030] Figure 2 This is a transmission electron microscope image of the high specific surface area nano calcium carbonate prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0031] Combined with Figure 1-2 As shown, the technical solution is further described;
[0032] Example 1
[0033] (1) The preparation of nano calcium carbonate with high specific surface area comprises the following steps:
[0034] Step 101. After calcium hydroxide emulsion is obtained by thorough reaction of calcium oxide and water, it is removed from impurities and aged to prepare slurry A with a concentration of 1.05 mol / L and a viscosity of 880 cP;
[0035] Step 102. After adding 8% of the crystal form control agent based on the dry weight of nano-calcium carbonate to the slurry prepared in step 101, pre-react at 20°C for 50 minutes to obtain slurry B, transfer slurry B to a high shear carbonization reactor, and introduce a flow rate of 1.2 m 3 / min lime kiln gas, and a stirring frequency of 50Hz. When the conductivity of slurry B is 3.1 ms / cm, the introduction of lime kiln gas into slurry B is stopped, and CaCO 3 -Ca(OH) 2 Linear intermediate slurry, wherein the lime kiln gas temperature is 40°C and the volume content of carbon dioxide in the lime kiln gas is 38%;
[0036] Step 103. The CaCO prepared in step 102 3 -Ca(OH) 2 The linear intermediate slurry and 7.0% of the dry weight of nano calcium carbonate dispersant were successively put into the stirring mill. 3 / min lime kiln gas, and a stirring frequency of 50Hz were used for secondary carbonization. The CaCO 3 -Ca(OH) 2 When the pH of the linear intermediate slurry was 7.0, the addition of CaCO 3 -Ca(OH) 2 The lime kiln gas is introduced into the linear intermediate slurry to obtain slurry C, wherein the lime kiln gas temperature is 32° C. and the volume content of carbon dioxide in the lime kiln gas is 36%;
[0037] Step 104. The slurry C prepared in step 103 is transferred to a modification kettle, and a modifier is added to the modification kettle for reaction. After the reaction is completed, slurry D is obtained. The slurry D is transferred to a finished product tank, and is successively subjected to filter pressing, dehydration, drying, and depolymerization to obtain high specific surface area nano calcium carbonate. In step 102, the crystal form control agent is a mixture of glucose and citric acid in a mass ratio of 1:3;
[0038] like Figure 1 As shown, the CaCO prepared in step 102 3 -Ca(OH) 2 The intermediate is a fiber network structure crystal, CaCO3 -Ca(OH) 2 The average crystal diameter of the intermediate is in the range of 10 nm, and the measured specific surface area is 102.570 m 2 / g;
[0039] In step 103, a mixture of dispersant maleic anhydride grafted polyisobutylene and sodium hexametaphosphate in a mass ratio of 1:4 is prepared;
[0040] In step 104, the modifier is a mixture of ethylene glycol palmitate and stearic acid in a mass ratio of 1:4.
[0041] (2) The preparation method of activated heavy calcium carbonate comprises the following steps: 1000 mesh vertical mill large calcite powder and an activator are sequentially put into a high-speed mixer at a mass ratio of 100:1, and the mixture is dispersed at high speed for 10 minutes at 102°C and 2200 rpm to obtain the activated heavy calcium carbonate.
[0042] The activator is a mixture of sodium polyacrylate and refined coconut oil in a mass ratio of 1:10.
[0043] (3) A multi-purpose silicone rubber base material is prepared according to the component list shown in Table 1, comprising the following steps: base rubber, high specific surface area nano calcium carbonate, and active heavy calcium carbonate are sequentially put into a reaction kettle, reacted for 3 hours at 110°C and -0.08Mpa, and then the silicone rubber base material is obtained after filling.
[0044] (4) The application adhesive is prepared according to the component list shown in Table 2, including the following steps: the above silicone adhesive base material and black color paste are put into a stirring kettle, and after vacuum stirring and dispersing for 10 minutes under the condition of -0.08Mpa, D-30 and D-90 are added in turn and vacuum stirred for 10 minutes at the original speed, and then KH-550 and KH-792 are added in turn and vacuum stirred for 10 minutes under the original conditions, and finally D80 is added and vacuum stirred for 10 minutes to obtain the application adhesive, which meets the requirements of low specific gravity, high strength and bright black.
[0045] Example 2
[0046] (1) The preparation of nano calcium carbonate with high specific surface area comprises the following steps:
[0047] Step 101. After calcium hydroxide emulsion is obtained by thorough reaction of calcium oxide and water, it is removed from impurities and aged to prepare slurry A with a concentration of 1.12 mol / L and a viscosity of 920 cP;
[0048] Step 102. After adding 7.2% of the crystal form control agent based on the dry weight of nano calcium carbonate to the slurry prepared in step 101, pre-react at 22°C for 40 minutes to obtain slurry B, transfer slurry B to a high shear carbonization reactor, and introduce a flow rate of 1.3m3 / min lime kiln gas, and a stirring frequency of 50Hz. When the conductivity of slurry B is 3.5 ms / cm, the introduction of lime kiln gas into slurry B is stopped, and CaCO 3 -Ca(OH) 2 Linear intermediate slurry, wherein the lime kiln gas temperature is 35°C and the volume content of carbon dioxide in the lime kiln gas is 38.7%;
[0049] Step 103. The CaCO prepared in step 102 3 -Ca(OH) 2 The linear intermediate slurry and 8.1% of the dry weight of nano calcium carbonate dispersant were successively put into the stirring mill. 3 / min lime kiln gas, and a stirring frequency of 50Hz were used for secondary carbonization. The CaCO 3 -Ca(OH) 2 When the pH of the linear intermediate slurry was 7.0, the addition of CaCO 3 -Ca(OH) 2 The lime kiln gas is introduced into the linear intermediate slurry to obtain slurry C, wherein the lime kiln gas temperature is 35° C. and the volume content of carbon dioxide in the lime kiln gas is 37.3%;
[0050] Step 104. The slurry C prepared in step 103 is transferred to a modification kettle, and a modifier is added to the modification kettle for reaction. After the reaction is completed, slurry D is obtained. The slurry D is transferred to a finished product tank, and is successively subjected to filter pressing, dehydration, drying, and depolymerization to obtain high specific surface area nano calcium carbonate. In step 102, the crystal form control agent is a mixture of glucose and citric acid in a mass ratio of 1:3;
[0051] In step 103, a mixture of dispersant maleic anhydride grafted polyisobutylene and sodium hexametaphosphate in a mass ratio of 1:4 is prepared;
[0052] In step 104, the modifier is a mixture of ethylene glycol palmitate and stearic acid in a mass ratio of 1:3.
[0053] (2) The preparation method of activated heavy calcium carbonate comprises the following steps: 1000 mesh vertical mill large calcite powder and activator are sequentially put into a high-speed mixer in a mass ratio of 100:1.3, and the mixture is dispersed at high speed for 10 minutes at 106°C and 2200 rpm to obtain the activated heavy calcium carbonate.
[0054] The activator is a mixture of sodium polyacrylate and refined coconut oil in a mass ratio of 1:11.
[0055] (3) A multi-purpose silicone rubber base material is prepared according to the component list shown in Table 1, comprising the following steps: base rubber, high specific surface area nano calcium carbonate, and active heavy calcium carbonate are sequentially put into a reaction kettle, reacted at 123°C and -0.08Mpa for 2.4 hours, and then the silicone rubber base material is obtained after filling.
[0056] (4) The application adhesive is prepared according to the component list shown in Table 2, including the following steps: the above silicone adhesive base material and black color paste are put into a stirring kettle, and after vacuum stirring and dispersing for 10 minutes under the condition of -0.08Mpa, D-30 and D-90 are added in turn and vacuum stirred for 10 minutes at the original speed, and then KH-550 and KH-792 are added in turn and vacuum stirred for 10 minutes under the original conditions, and finally D80 is added and vacuum stirred for 10 minutes to obtain the application adhesive, which can be used as a medium-strength structural adhesive.
[0057] Example 3
[0058] (1) The preparation of nano calcium carbonate with high specific surface area comprises the following steps:
[0059] Step 101. After calcium hydroxide emulsion is obtained by thorough reaction of calcium oxide and water, it is prepared into slurry A with a concentration of 1.2 mol / L and a viscosity of 998 cP after impurity removal and aging;
[0060] Step 102. After adding 5-8% of the crystal form control agent based on the dry weight of nano calcium carbonate to the slurry prepared in step 101, pre-react at 23°C for 23 minutes to obtain slurry B, transfer slurry B to a high shear carbonization reactor, and introduce a flow rate of 1.5m 3 / min lime kiln gas, and a stirring frequency of 50Hz. When the conductivity of slurry B is 3.5 ms / cm, the introduction of lime kiln gas into slurry B is stopped, and CaCO 3 -Ca(OH) 2 Linear intermediate slurry, wherein the lime kiln gas temperature is 38°C and the volume content of carbon dioxide in the lime kiln gas is 38.1%;
[0061] Step 103. The CaCO prepared in step 102 3 -Ca(OH) 2 The linear intermediate slurry and 6.3% of the dry weight of nano calcium carbonate dispersant were successively put into the stirring mill. 3 / min lime kiln gas, and a stirring frequency of 50Hz were used for secondary carbonization. The CaCO 3 -Ca(OH) 2 When the pH of the linear intermediate slurry was 7.0, the addition of CaCO 3-Ca(OH) 2 The lime kiln gas is introduced into the linear intermediate slurry to obtain slurry C, wherein the lime kiln gas temperature is 32.1°C and the volume content of carbon dioxide in the lime kiln gas is 35.5%;
[0062] Step 104. The slurry C prepared in step 103 is transferred to a modification kettle, and a modifier is added to the modification kettle for reaction. After the reaction is completed, slurry D is obtained. The slurry D is transferred to a finished product tank, and is successively subjected to filter pressing, dehydration, drying, and depolymerization to obtain high specific surface area nano calcium carbonate. In step 102, the crystal form control agent is a mixture of glucose and citric acid in a mass ratio of 1:3;
[0063] In step 103, a mixture of dispersant maleic anhydride grafted polyisobutylene and sodium hexametaphosphate in a mass ratio of 1:4 is prepared;
[0064] In step 104, the modifier is a mixture of ethylene glycol palmitate and stearic acid in a mass ratio of 1:4.
[0065] (2) The preparation method of activated heavy calcium carbonate comprises the following steps: 1000 mesh vertical mill large calcite powder and activator are sequentially put into a high-speed mixer in a mass ratio of 100:1.5, and the mixture is dispersed at high speed for 10 minutes at 108°C and 2200 rpm to obtain the activated heavy calcium carbonate.
[0066] The activator is a mixture of sodium polyacrylate and refined coconut oil in a mass ratio of 1:12.
[0067] (3) A multi-purpose silicone rubber base material is prepared according to the component list shown in Table 1, comprising the following steps: base rubber, high specific surface area nano calcium carbonate, and active heavy calcium carbonate are sequentially put into a reaction kettle, reacted for 3 hours at 146°C and -0.08Mpa, and then the silicone rubber base material is obtained after filling.
[0068] (4) The application adhesive is prepared according to the component list shown in Table 2, including the following steps: the above silicone adhesive base material and black color paste are put into a stirring kettle, and after vacuum stirring and dispersing for 10 minutes under the condition of -0.08Mpa, D-30 and D-90 are added in turn and vacuum stirring is maintained at the original speed for 10 minutes, and then KH-550 and KH-792 are added in turn and vacuum stirred for 10 minutes under the original conditions, and finally D80 is added and vacuum stirred for 10 minutes to obtain the application adhesive, which is mainly used in the circulation field.
[0069] Table 1 Silicone rubber base material composition
[0070]
[0071] Table 2 Application glue components
[0072]
[0073] The silicone base material and the application glue prepared in Examples 1-3 were tested for mechanical properties, and the test results are shown in Table 3 below.
[0074] Table 3 Mechanical properties test table of silica gel base material and application glue in Example 1-3
[0075]
[0076]
[0077] From the test results in Table 3 above, it can be seen that the present invention can effectively control the average particle size of nano calcium carbonate crystals within the range of 8-10nm and the specific surface area of 100-120m after secondary carbonization of calcium hydroxide emulsion by using the composite crystal form control agent. 2 / g, the crystal form is controlled to be calcite type, and the shape is cubic cluster. In the process of preparing silicone adhesive base material, high specific surface area nano calcium carbonate crystals have strong dispersibility and large specific surface area, and can completely replace gas phase carbon black or gas phase silica. It has the advantages of high reinforcement, high compatibility and easy processing. By compounding it with activated heavy calcium carbonate, it can effectively improve the miscibility of ultrafine particles, improve the dispersion state of silicone adhesive, and enhance the mechanical properties of silicone adhesive. After being prepared into application adhesive, it is more in line with the use requirements of different scenarios, which can effectively reduce the production cost of application adhesive and has good economic benefits.
[0078] The above are only embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A multi-purpose silicone rubber base material, characterized in that: The composition is composed of the following components by weight: 37-62 parts of base glue, 18-38 parts of nano calcium carbonate with high specific surface area, 5-45 parts of active heavy calcium carbonate, and the base glue is 20000mPa﹒s terminal hydroxyl polydimethylsiloxane; The method for preparing nano calcium carbonate with high specific surface area comprises the following steps: Step 101. After calcium hydroxide emulsion is obtained by thorough reaction of calcium oxide and water, it is removed from impurities and aged to prepare a slurry A with a concentration of 1.0-1.2 mol / L and a viscosity of 800-1000 cP; Step 102. After adding the crystal form control agent to the slurry A prepared in step 101, pre-react at 20-23° C. for 20-50 minutes to obtain slurry B, transfer slurry B to a high shear carbonization kettle, introduce lime kiln gas, and perform a primary carbonization at a stirring frequency of 50 Hz, and simultaneously measure the conductivity of slurry B to determine the endpoint of the primary carbonization reaction. After reaching the endpoint of the primary carbonization reaction, a CaCO3-Ca(OH)2 linear intermediate slurry is obtained; Step 103. The CaCO3-Ca(OH)2 linear intermediate slurry and the dispersant prepared in step 102 are sequentially put into a stirred mill, and then lime kiln gas is introduced, and secondary carbonization is performed under the condition of a stirring frequency of 50 Hz, and the pH value of the CaCO3-Ca(OH)2 linear intermediate slurry is measured at the same time to determine the endpoint of the secondary carbonization reaction. When the endpoint of the secondary carbonization reaction is reached, slurry C is obtained; Step 104. The slurry C prepared in step 103 is transferred to a modification kettle, and a modifier is added to the modification kettle for reaction. After the reaction is completed, slurry D is obtained. The slurry D is transferred to a finished product tank, and is successively subjected to filter pressing, dehydration, drying, and depolymerization to obtain nano calcium carbonate with a high specific surface area; In step 104, the average particle size of the prepared nano calcium carbonate crystals is controlled in the range of 8-10 nm, and the average specific surface area is 100-120 m 2 / g; In step 102, the crystal form control agent is a mixture of glucose and citric acid in a mass ratio of 1:3, and the amount of the crystal form control agent added is 5-8% of the dry weight of calcium carbonate; In step 103, the dispersant is a mixture of maleic anhydride grafted polyisobutylene and sodium hexametaphosphate in a mass ratio of 1:4, and the amount of the dispersant added is 6.0-10.0% of the dry weight of the nano-calcium carbonate; In step 104, the modifier is a mixture of ethylene glycol palmitate and stearic acid in a mass ratio of 1:2-4.
2. A multi-purpose silicone adhesive base material according to claim 1, characterized in that: The preparation method of activated heavy calcium carbonate comprises the following steps: 1000-mesh vertical mill large calcite powder and an activator are sequentially put into a high-speed mixer at a mass ratio of 100:1-1.5, and the mixture is dispersed at a high speed for 10 minutes at 100-110°C and 2200rpm to obtain the activated heavy calcium carbonate.
3. A multi-purpose silicone adhesive base material according to claim 2, characterized in that: The activator is a mixture of sodium polyacrylate and refined coconut oil in a mass ratio of 1:10-12.
4. A multi-purpose silicone adhesive base material according to claim 1, characterized in that: In step 102, the temperature of the lime kiln gas is 30-40°C, the flow rate of the lime kiln gas is 1.2-1.5 m3 / min, and the volume content of carbon dioxide in the lime kiln gas is 38-40%.
5. A multi-purpose silicone adhesive base material according to claim 1, characterized in that: In step 102, when the conductivity of slurry B is measured to be 3-4 ms / cm, the primary carbonization reaction reaches the end point, and the introduction of lime kiln gas into slurry B is stopped.
6. A multi-purpose silicone adhesive base material according to claim 1, characterized in that: In step 103, when the pH value of the CaCO3-Ca(OH)2 linear intermediate slurry is measured to be 7.0, the secondary carbonization reaches the reaction endpoint, and the introduction of lime kiln gas into the CaCO3-Ca(OH)2 linear intermediate slurry is stopped.
7. A method for preparing a multi-purpose silicone adhesive base according to any one of claims 1 to 6, characterized in that: The process comprises the following steps: putting base glue, nano calcium carbonate with high specific surface area and active heavy calcium carbonate into a reaction kettle in sequence, reacting for 2-3 hours under the conditions of 100-150°C and -0.08Mpa, and then filling to obtain the silicone glue base material.
Citation Information
Patent Citations
Preparation method of nano calcium carbonate for production of neutral transparent silicone adhesive
CN108163878A